Al-bāṭiniyyah Values and Character Formation in Modern Education: A Hermeneutic Study of Imam Al-Zarnūjī's Thought - Ninoersy, Tarmizi; Isnayanti, Nelli (LP. Ma'arif Janggan Magetan, 2025)
Education in today’s modern world often faces challenges such as a lack of motivation to learn and a decline in students’ moral integrity. In today's educational landscape, many systems place too much emphasis on cognitive achievement, neglecting the emotional and spiritual development of students. This article examines the Al-bāṭiniyyah Values and Character Formation in Modern Education: A Hermeneutic Study of Imam Al-Zarnūjī's Thought. Drawing from Imam Al-Zarnūjī’s Ta‘līm al-Muta‘allim, which emphasizes the importance of sincere intention (niyyah) in acquiring knowledge, the study explores how spiritual values can be incorporated into modern education. Using a hermeneutic approach and a literature review, the study analyzes Al-Zarnūjī’s principles and compares them with Thomas Lickona’s character education model. The findings reveal that the Al-bāṭinīyah approach offers a transformative, holistic educational method that balances cognitive, affective, and spiritual dimensions. It emphasizes values such as sincerity, humility, and ethical discipline as being essential to character formation. The study concludes that the Al-bāṭinīyah principle enriches not only Islamic education but also contributes universally to modern character education, fostering ethical awareness and human dignity.